A REVIEW OF THE SOCIAL DIMENSIONS OF THE STUDY OF THE PROPHET’S صلى الله عليه وسلم BIOGRAPHY AND CONTEMPORARY APPLICATIONS - Dr. Abdul Ghaffar; Muhammad Abdullah (International Journal of Contemporary Issues in Social Sciences, 2024)
Sociology1 is a science that mainly deals with behavioral ethics, human behavior and interpersonal relations whether they are national or international diplomacy. Whereas psychology, human psychology discusses the construction and formation of various social institutions. After identifying the problems, studies are presented on it. Due to globalization these become different types. Especially during the current wave of epidemics (Covid-19), these problems have been divided into more types. Especially where the 21st century has brought scientific inventions, cultural development, fastest travel facilities, along with this, social and moral problems have also arisen due to which humanity has become a victim of temptation and corruption and it is trying to solve such problems, while in these same years slogans are being raised about basic human rights, where it has been positive effects, as well as ideas devoid of morals and values have also affected humanity.